Environmental sanitation and risk of stunting among under-five children: A cross-sectional study - Sarwoko, Sabtian (School of Health Sciences Al-Ma'arif, 2026)
Background: Stunting remains a major public health problem in low- and middle-income countries, including Indonesia, where environmental sanitation conditions continue to pose significant health risks. Inadequate access to safe drinking water, proper sanitation facilities, and appropriate waste management increases children’s exposure to recurrent infections that may impair linear growth during the first 1,000 days of life. Despite national efforts to accelerate stunting reduction, sanitation-related risk factors remain prevalent in rural priority districts. Objective: This study aimed to analyze the association between environmental sanitation and the risk of stunting among children under five years of age in Jayapura Subdistrict, Ogan Komering Ulu Timur Regency, Indonesia. Methods: An analytical cross-sectional study was conducted between March and July 2022 involving 280 children aged 12–59 months selected from a population of 1,026 eligible children. Data on drinking water quality, toilet use, solid waste management, and wastewater management were collected through structured interviews and direct household observations. Stunting status was determined using height-for-age Z-scores based on WHO Child Growth Standards. Data were analyzed using descriptive statistics and Fisher’s Exact Test at a 95% confidence level. Results: The prevalence of stunting was 13.6%. Poor drinking water quality, lack of toilet use, inadequate solid waste management, and improper wastewater management were significantly associated with stunting (p = 0.001). Children living in households with unsafe drinking water had a stunting prevalence of 25.6%, compared with 4.9% among those with safe water. The highest proportion of stunting (28.9%) was observed among children exposed to poor wastewater management. Conclusion: Environmental sanitation factors are significantly associated with stunting among under-five children. Strengthening access to safe water, improved sanitation facilities, and proper waste and wastewater management is essential to reduce stunting risk in rural priority areas. Integrated environmental and nutritional interventions are recommended to accelerate sustainable stunting reduction.